Acute hepatitis C infection in HIV‐negative men who have sex with men. Issue 6 (21st November 2014) - McFaul, K.; Maghlaoui, A.; Nzuruba, M.; Farnworth, S.; Foxton, M.; Anderson, M.; Nelson, M.; Devitt, E.
Summary Acute hepatitis C infection is recognized in HIV‐infected men who have sex with men (MSM), but the risk in HIV‐negative MSM remains unclear. We evaluated a population of MSM with acute hepatitis C. From January 2010 to May 2014, all cases of HCV antibody positive HIV‐negative MSM were identified. European AIDS Network criteria were applied to determine acute infection, and 44 individuals fulfilled the criteria for acute hepatitis C. Ten were RNA negative at baseline and classed as prior spontaneous clearance. 15 (34.1%) had a previously negative HCV antibody within 1 year. 11 (25.0%) had significant elevation in ALT levels, and 18 (40.9%) were clinically diagnosed from risk exposure and history. Median age was 37 years (range 24–75). 41 (93.2%) individuals reported unprotected anal sex, 36 with (87.8%) both insertive and receptive intercourse, 4 (9.8%) with receptive intercourse, 1 (2.4%) with insertive intercourse, and no data were recorded for 3 (7.3%) patients. Individuals had an average of 7.3 reported (median 2, range 1–100) partners. 12 (27.3%) engaged in group sex, 11 (25.0%) practised fisting, 11 (25.0%) admitted using drugs during sexual activity, 16 (36.4%) reported nasal, and 9 (20.5%) reported injection drug use. 14 (31.8)% had unprotected sex whilst under the influence of recreational drugs. 29 individuals were aware of a partner's status. 2 (4.5%) individuals had sexual contact with a known HCV monoinfected partner, 13 (29.5%) with a HIV monoinfected partner and 6 (13.6%) with a HCV/HIV coinfected partner. 9 (20.5%) reported a partner/partners with no known infection. No data were available in 14 (31.8%) individuals. 13 (29.5%) individuals had a coexisting STI at the time of acute HCV diagnosis. 8 (18.2%) received HIV postexposure prophylaxis (PEP) within the 6 months prior to the HCV diagnosis (2 were participants in a HIV pre‐exposure prophylaxis trial). 15 (34.1%) individuals achieved spontaneous clearance of HCV, and 11 patients received HCV treatment. Similar to the ongoing epidemic of acute HCV infection in HIV+ MSM, HIV‐negative MSM remain at risk.